Ecological Education As The Most Important Problem Of Modern Education (Texas Journal of Multidisciplinary Studies, 2024)
In this article, the impact of environmental education - natural processes on the mind and worldview of young people was analyzed directly from the author's point of view. Environmental education is a form and part of education, the main goal of which is to observe the environment in the young generation, which is described in the article